2020
DOI: 10.1097/ta.0000000000002988
|View full text |Cite
|
Sign up to set email alerts
|

Bile duct clearance and cholecystectomy for choledocholithiasis: Definitive single-stage laparoscopic cholecystectomy with intraoperative endoscopic retrograde cholangiopancreatography versus staged procedures

Abstract: BACKGROUND Clinical equipoise exists regarding optimal sequencing in the definitive management of choledocholithiasis. Our current study compares sequential biliary ductal clearance and cholecystectomy at an interval to simultaneous laparoendoscopic management on index admission in a pragmatic retrospective manner. METHODS Records were reviewed for all patients admitted between January 2015 and December 2018 to a Swedish and an Irish university hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Several studies have shown better outcomes in those who received early cholecystectomy following duct clearance for gallstone pancreatitis, and the Tokyo Guidelines (2018) advise index admission cholecystectomy in this instance [26,27]. A recent comparison of one-stage ERCP and cholecystectomy versus index admission ERCP with planned interval elective day-case cholecystectomy demonstrated a readmission rate over 20% in the latter group, due to complications relating to the retained gallbladder as a stone reservoir [28]. Regrettably, our current data did not report readmission rate, but given the overlap in patient populations, we would expect similar rates of disease recidivism in the non-operated cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown better outcomes in those who received early cholecystectomy following duct clearance for gallstone pancreatitis, and the Tokyo Guidelines (2018) advise index admission cholecystectomy in this instance [26,27]. A recent comparison of one-stage ERCP and cholecystectomy versus index admission ERCP with planned interval elective day-case cholecystectomy demonstrated a readmission rate over 20% in the latter group, due to complications relating to the retained gallbladder as a stone reservoir [28]. Regrettably, our current data did not report readmission rate, but given the overlap in patient populations, we would expect similar rates of disease recidivism in the non-operated cohort.…”
Section: Discussionmentioning
confidence: 99%
“…[25,26] In cholelithiasis, LC with intraoperative ERCP has been proved as a safe and feasible strategy for the management of cholelithiasis and choledocholithiasis, with less cost, shorter length of hospital stays, and shorter anesthesia time. [27][28][29] As for PEP, research is mainly focused on prophylaxis medications, such as indomethacin or diclofenac. [30] For "sphincter dysfunction," the necessity of ERCP for patients with sphincter of Oddi dysfunction (SOD) remains a controversial issue.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, most patients deferred from an index admission cholecystectomy are older, burdened by comorbidities, and frail, which makes managing CBD stone-related complications even more challenging. 21,[23][24][25] With a growing elderly patient population worldwide, gallstone-related diseases and interventions will also increase; this includes cholecystectomy for acute cholecystitis, which has a threefold higher risk of CBD stones than elective cholecystectomy. 26,27 Currently, guidelines do not make a distinction in the optimal timing of acute cholecystectomy for cholecystitis when comparing elderly and younger patients.…”
Section: Ercp Without Cholecystectomymentioning
confidence: 99%